2023
DOI: 10.1111/cpr.13403
|View full text |Cite
|
Sign up to set email alerts
|

Targeting soluble epoxide hydrolase promotes osteogenic–angiogenic coupling via activating SLIT3/HIF‐1α signalling pathway

Abstract: Type H vessels have recently been identified to modulate osteogenesis. Epoxyeicostrioleic acids (EETs) have an essential contribution to vascular homeostasis. However, whether increased EETs with soluble epoxide hydrolase (sEH) inhibitor TPPU enhance the coupling of angiogenesis and osteogenesis remains largely unknown. The effects of TPPU on cross‐talk between co‐cultured human umbilical vein endothelial cells (HUVECs) and human dental pulp stem cells (hDPSCs), and on long bone growth and calvarial defect rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Exogenous systemic administration of EETs also promotes liver regeneration in mice [ 12 ]. Our previous experiments also confirmed that EETs enhance the formation of new bone, collagen fibers and vascular structures in a mouse calvarial defect model [ 13 ]. However, it has not been reported whether EETs can promote the coupling of angiogenesis and odontogenesis, thereby promoting pulp tissue regeneration.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Exogenous systemic administration of EETs also promotes liver regeneration in mice [ 12 ]. Our previous experiments also confirmed that EETs enhance the formation of new bone, collagen fibers and vascular structures in a mouse calvarial defect model [ 13 ]. However, it has not been reported whether EETs can promote the coupling of angiogenesis and odontogenesis, thereby promoting pulp tissue regeneration.…”
Section: Introductionsupporting
confidence: 75%
“…Our in vitro results suggested that HIF-1α plays a pivotal role in POTCs. Recently, we have demonstrated that TPPU increases HIF-1α levels in cocultured HUVECs and hDPSCs by activating SLIT3 in hDPSCs [ 13 ]. HIF-1α, as a transcription factor, could regulate the expression of VEGF and TGF-β [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our in vitro and in vivo results suggested that HIF-1α plays a pivotal role in POTCs. Recently, we have demonstrated that TPPU increases HIF-1α levels in cocultured HUVECs and hDPSCs by activating SLIT3 in hDPSCs [13]. Here, we further showed that TPPU-upregulated HIF-1α is also involved in odontogenesis and angiogenesis with increased expression of VEGFR2 in ECs and TGF-β, DSPP, and DMP-1 in MSCs.…”
Section: Discussionsupporting
confidence: 54%
“…Exogenous systemic administration of EETs also promotes liver regeneration in mice [12]. Our previous experiments also con rmed that EETs enhance the formation of new bone, collagen bers and vascular structures in a mouse calvarial defect model [13]. However, it has not been reported whether EETs can promote the coupling of angiogenesis and odontogenesis, thereby promoting pulp tissue regeneration.…”
Section: Introductionmentioning
confidence: 77%